Corrigendum to: Analysis of landscape microclimate and green space transformation strategy for old residential areas——case: Luoliu community - Li Yihan; Wang Jingjing; Gou Aiping; Wang Jiangbo (E3S Web of Conferences)
The name of a new author, Jingjing Wang, has been added and the order of authors has been modified to better reflect the individual contribution of each author in the work.